2015
DOI: 10.1007/s12195-015-0384-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cell Membrane Capacitance is the Dominant Mechanism of Stretch-Dependent Conduction Slowing in the Rabbit Heart: A Computational Study

Abstract: Volume loading of the cardiac ventricles is known to slow electrical conduction in the rabbit heart, but the mechanisms remain unclear. Previous experimental and modeling studies have investigated some of these mechanisms, including stretch-activated membrane currents, reduced gap junctional conductance, and altered cell membrane capacitance. In order to quantify the relative contributions of these mechanisms, we combined a monomain model of rabbit ventricular electrophysiology with a hyperelastic model of pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…Some studies have shown a dependence of the capacitance of the cardiomyocyte cell membrane on local stretch ( Mills et al., 2008 ). Although the sparsity of experimental data leads to ambiguities in the optimal choice of model, we follow here the Hill function formalism previously introduced for ventricular cells ( Oliveira et al., 2015 ): …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown a dependence of the capacitance of the cardiomyocyte cell membrane on local stretch ( Mills et al., 2008 ). Although the sparsity of experimental data leads to ambiguities in the optimal choice of model, we follow here the Hill function formalism previously introduced for ventricular cells ( Oliveira et al., 2015 ): …”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that intercellular connectivity at gap junctions may be increased ( Zhuang et al., 2000 ) or decreased ( Kamkin et al., 2005 ; Mills et al., 2008 ) by stretch, whereas other have proposed that intracellular conductivity increases with (moderate) strains ( McNary et al., 2008 ) or is affected by mechanical stress ( Loppini et al., 2018 ). Other studies have instead modelled the geometric effect of stretch by assuming a reduction in the number of gap junctions per unit length of chronically dilated atrial myocardium ( Kuijpers et al., 2007 ) or alterations in the space constant of the tissue ( Oliveira et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In order to account for the slowdown of the action potential (AP) propagation upon muscle stretch [26][27][28], the normalized capacitance of the cell membranes C was assumed being strain-dependent [19]. The strain-dependence was shown to be associated with a strain-dependent recruitment of caveolae into the cell membrane causing an increase in its capacitance of and the electrical time constant even when stretch-activated ionic channels were inactivated [27].…”
Section: Model Descriptionmentioning
confidence: 99%
“…The effect of the strain of myocardial tissue on the AP propagation velocity, so-called mechano-electrical feedback, was also not taken into account in most of those models with a few exceptions. The attempts of the modelling of the strong electromechanical coupling including the mechano-electrical feedback were made by a number of research groups [11,[14][15][16][17][18][19], however, the assumptions used in these models were not always supported by experimental observations, or only the mechano-calcium feedback was considered while a direct influence of strain on the speed of activation propagation was not taken into account. Another important feature of the force-frequency relation in cardiac muscle that was not demonstrated by previous simulations is the acceleration of force relaxation at increased stimulation frequency [20].…”
Section: Introductionmentioning
confidence: 99%
“…As hA-CMs are likely to have very few (if any) T-tubules in cAF, slower Ca 2+ diffusion is thought to exacerbate dyssynchrony of the AP and CaT, thus potentially contributing to alternans. At the tissue level, increased capacitance of CM membrane causes conduction slowing ( Oliveira et al, 2015 ).…”
Section: Arrhythmogenic Mechanisms Of Afmentioning
confidence: 99%